Performance testing: evaluating an RFID library inventory reader. (10th December 2007) - Golding, Paul; Tennant, Vanesa
Numerous studies have been performed in supply chain environments to determine the performance requirement to achieve a near 100% read rate. However the literature on testing in the library environment is sparse. This study examines the operational efficiencies of a RFID library reader. The factors examined included angle directionality sensitivity, read distance and tag location. The findings suggested that the performance of the inventory system degrades significantly as the angle directionality moves from 0 to 60 degrees. The read distance varied from vendor specification. The findings provide empirical insight into the performance of an RFID reader in an operating environment.